Development of neuromuscular specificity in the grasshopper embryo: guidance of motoneuron growth cones by muscle pioneers - Ball, EE (J Neurosci, 1985)
In the grasshopper embryo, neuromuscular specificity develops between individual identified motoneurons whose cell bodies are located in the central nervous system, and specific skeletal muscles in the periphery. We previously reported on a class of large mesodermal cells, called muscle pioneers (MPs), that arise early in development (Ho, R. K., E. E. Ball, and C. S. Goodman (1983) Nature 301: 66–69). We suggested that the MPs might be involved in orchestrating the coordinated development of nerve and muscle. In this paper, we describe the development of the MP for coxal muscle 133a in the metathoracic limb bud, and its innervation by two excitatory motoneurons (fast, Df, and slow, Ds). Although many motoneuron growth cones extend out of nerve 5 and quite likely come in contact with the 133a MP between 35% and 45% of development, only Df and Ds display a high affinity for its surface; the other motoneurons innervate more distal leg muscles. When the 133a MP is ablated before arrival of motoneurons in the limb bud, the Df growth cone extends past the location where it normally gets off nerve 5 and continues to extend distally along the same pathway taken by its sibling motoneuron. Although there is a mass of small mesodermal cells in the area where the differentiated coxal muscle 133a normally forms, evidently it does not provide the necessary guidance cue for the Df growth cone. These results indicate the important role played by MPs in the specific guidance of motoneuron growth cones in the grasshopper embryo.